Investigating the effect of synthesis selection on O3-sodium layered oxide structural changes and electrochemical properties - Acebo, L.; Drewett, N. E.; Saurel, D.; Bonilla, F.; Rojo, T.; Galceran, M. (Frontiers in Chemistry, 2023)
Transition metal (TM) layered oxides constitute a promising family of materials for use in Na-ion battery cathodes. Here O3-Na (Ni1/3Mn1/3Fe1/3) O2 was synthesised using optimised sol-gel and solid-state routes, and the physico- and electrochemical natures of the resulting materials were thoroughly studied. Significant differences in electrochemical behaviour were observed, and the use of in operando XRD determined this stemmed from the suppression of the P3 phase in the sol-gel material during cycling. This was attributable to differences in the degree of transition metal migration in the materials ensuing from the selection of synthetic route. This demonstrates that not only the choice of material, but also that of synthesis route, can have dramatic impact on the resulting structural and electrochemical nature, making such considerations critical in the future development of advanced Na-ion cathode materials.